The Grey Men - Orme, David (Stanley Thornes Publishers Ltd, 1998)
Martin and Jade are on their way home when they see the spaceship. The Grey Men are looking for someone. And Martin wants to go with them$1! =s
Keywords: Juvenile Fiction